A complex systems approach to understand the influence of community-based interventions in spatial segregation patterns in Colombia (2023)
Latin America is a region where urbanization processes are strongly transforming cities, turning small and medium-sized cities into large cities. These transitions represent a challenge in the search to build fairer and more sustainable cities. Among these challenges is the search to close social inequality gaps. These inequalities can sometimes be generated by the processes of social conformation of populations, especially the most vulnerable along the cities. In Latin America, these dynamics are strongly rooted in segregation processes, a recurrent pattern in the region's cities. Although segregation is a social phenomenon, it is a process intrinsically related to space. Community-based interventions have been widely used throughout Latin American cities as a strategy to break patterns of segregation and reduce inequality gaps. However, understanding the effects of these interventions on the communities they are intended to benefit presents a challenge. The multidimensional nature of segregation and its intrinsic relationship with space is a challenge in understanding its effects on possible social processes such as selective migration. This thesis aims to develop a robust understanding of segregation and the effects that community-based interventions can have on these dynamics. Starting from a conceptual framework rooted in complex systems, this thesis seeks to understand the relationships between segregation, space, and community-based interventions in Colombia, using as a case study the case of TransMiCable in Bogotá. The first part presents a characterization of the built environment in Latin America, understanding the importance of space in the configuration of segregation. The heterogeneity of the built environment allows visualizing the existing differences between countries and cities with different characteristics, which show the different challenges that public policy actors must face. Within this characterization, associations with social determinants of health were identified, which provide evidence of the importance of space configuration in inequality and poverty processes. The second part presents a characterization of spatial segregation patterns in Colombia, one of the most unequal countries in the region. Segregation patterns show a non-uniform distribution of the most educated people in cities, as well as Afro-Colombians, mulattos, or blacks compared to mestizos. Additionally, the most isolated people and employees are isolated from other groups. These patterns show strong concentration processes of wealth in specific cities and with the transitions of segregation processes towards more focused segregation patterns within cities. These patterns are related to space, where more fragmented cities exhibit a more uniform distribution and less isolation. Finally, the last part analyzes the case study of the cable car in Ciudad Bolivar, a community intervention carried out in Bogotá led by a community initiative, which, through community participation and social cohesion, achieved the creation of the entire urban intervention. The intervention, beyond achieving an improvement in living conditions, air quality, and transport time, has generated greater social cohesion and strengthening of the social tissue. These elements represent a way to attenuate processes such as selective migration, where a transition of social capital and a construction of more cohesive interpersonal networks can represent a strategy to favor the most vulnerable populations. This premise seeks to generate evidence on the importance of social capital and the social tissue in attenuating selective migration processes that lead to the formation of segregation patterns in cities. The case of TransMiCable in Bogotá is an example of how citizen participation and an intervention accompanied by the community in its design and implementation can help mitigate selective migration patterns, where in the 5 years since its inauguration, it has favored the migration of vulnerable populations to less segregated areas compared to more segregated areas.